Role of mitochondrial DNA in oxidative damage induced by sodium arsenite in human bronchial epithelial cells. Issue 18 (17th September 2019) - Wu, Jing; Ni, Yiping; Wang, Xiaojuan; Yang, Qianlei; Mao, Jiayuan; Tong, Jian; Zhang, Jie; An, Yan
ABSTRACT: Long-term exposure to sodium arsenite was found to induce malignant transformation in human bronchial epithelial (HBE) cell line as evidenced by elevated ROS levels. Although chronic sodium arsenite-induced HBE cell line transformation was associated with elevated ROS generation, it was of interest to determine whether acute sodium arsenite exposure also initiated pulmonary damage. Thus, the aim of this study was to investigate oxidative-stress-related pulmonary damage using a human bronchial epithelial (HBE) cell line. Incubation of ρ + -HBE (in the presence of mitochondrial DNA) cells with various concentrations of sodium arsenite, significantly increased ROS and MDA levels accompanied by decreased SOD activity in a concentration-dependent manner. In contrast, treatment of ρ – HBE (without mitochondrial DNA) cells various concentrations of sodium arsenite a reduction in ROS and MDA levels were noted. However, the SOD activity remained decreased in ρ – HBE cells. This was accompanied by a significant rise in HO-1 protein expressions levels in both cell types with greater changes ρ – HBE cells at the lower sodium arsenite concentrations. Data indicate that acute sodium arsenite exposure exerted a greater effect ρ – HBE cells suggesting that absence of mitochondrial DNA appears to enhance sensitivity to the oxidant actions of inorganic As.